Bibliometric Review on Corporate Social Responsibility of the Food Industry - Mingli He; Weiping Yu; Xiaoyun Han (Journal of Food Quality)
Corporate social responsibility (CSR) in the food industry has received increasing attention in recent years. Many scholars have paid attention to case studies and other empirical analyses in this field, but there is no systematic or scientific literature review. The purpose of this study is to quantitatively evaluate the knowledge structure, research hotspots, and development history in CSR in the food industry. After searching, screening, and commenting, 498 articles were left for citation analysis, co-citation analysis, and co-word analysis. The main findings of the research are as follows: (1) The overall development status of the research in the field. The analysis of the three fields that constitute the knowledge structure. (2) Research in this field has become a hot spot, but the research is rather scattered, and the scholars and experts do not have a special research core. (3) The keywords’ cluster results in 9 clustering tags, which are further grouped into 7 groups. The research of the scholars focuses on the food supply chain, consumer perception, and social media communication. (4) The research topics in this field focus on environmental responsibility, nutrition and health, and food safety. The research results show that future research should be more in-depth and reflect the new characteristics of the Internet, digitalization, and big data.